Application of Tabata Training to Improve Physical Fitness and DanceSports Skills for Guangdong University Students - Li , Linjing; Tasnaina, Nopporn; Hongseanyatham, Prakit (International Journal of Sociologies and Anthropologies Science Reviews, 2024)
Background and Aims: With the continuous popularization of all-round education, the status of physical education is gradually improving. DanceSports, as a relatively new course, has important aesthetic value in higher education and meets the specific needs of all-around education in colleges and universities. Dance Sport has a unique aesthetic value compared with other traditional sports. There were many problems and limitations in dance such as course content and training models. Especially the improvement of endurance. The traditional training usually applied moderate-intensity continuous training (MICT) to train the Dance Sport athletes which could not meet the demand of aerobic and anaerobic endurance for them during competition. The new procedure to improve both aerobic and anaerobic endurance was the Tabata training method which was a high-intensity interval Training (HIIT) procedure that could be more advantageous than the MICT training procedure, the researcher plans to create a teaching model through the Tabata training method to prove this. This paper aims to Construct a DanceSports teaching program applying Tabata training to improve physical abilities and performance in DanceSports for university students. Materials and Methods: The program of Tabata training added to the DanceSports teaching program was developed by interviewing 9 experts and a consensus of 19 experts with the Delphi method. The validity of the program was average.90 (.60 -1.00) and efficiency were 71.6/71.40. The two groups' pretest-posttest experimental was used. The subjects were 60 students studying DanceSports in physical education courses at the university level at Guangdong University. They were divided into two groups by systematic based on physical fitness test scores. The Dance Sport with Tabata training was a treatment in the experimental group and the Dance Sport with MICT training was a treatment in the control group, the experiment operated for 8 weeks, 2 sessions a week with 2 hours a session. The research tools were the Physical fitness tests, Dance Sport performance test, the added Tabata training in the DanceSports teaching program, and Traditional MICT added in the DanceSports teaching program. The data analysis used a paired t-test and an independent t-test to compare the results of the experiment. Results: 1) The physical fitness in the Tabata training group was higher than in the MICT group at 0.05 significant level at the vital capacity, sprint, flexibility, long jump, abdominal muscle strength, and long-distance running. 2) The DanceSports performance in the Tabata training group was higher than in the MICT group at 0.05 significant level at the posture, dance hold, balance, foot action, Latin actions, general actions, and spins and turns. Conclusion: The Tabata training was significant in improving physical fitness and DanceSports performance in university students than the MICT training in the program. I could prove that the Tabata training procedure can enhance the physical fitness and DanceSports performance of university students and might be applied to elite DanceSports players’ training.